Today's boys, tomorrow's men' : a short history of the Boys' Brigade of Britain, with further reference to the Boys' Brigade in South Africa (circa 1880s-1980s) - Adonis, Dan Frederick (Department of Historical Studies, 2014)
Includes bibliographical references.